Cash Flow, Financial Leverage, and Current Ratio Towards Corporate Valueatfood and Beverage - Sylvia Ngatimo; Sri Cintia Dewi; Mila Yulia Herosian (Institute of Computer Science (IOCS), 2021)
A slowing economy has an impact on public consumption. Where, the middle and upper economic community reduces their consumption policy, such as the community reducing expenditure on all necessities except household needs, so that the sales level decreases and economic growth slows down which can lead to inflation, making people careful in their daily expenses. The purpose of this study was to determine the effect of cash flow, financial leverage and current ratio on company value in the Food and Beverages industry sector companies listed on the Indonesia Stock Exchange in 2014-2019. This study uses a quantitative research approach. Data collection techniques using documentation. The population used in this study are 26 companies in the Food and Beverages industry sector which are listed on the Indonesia Stock Exchange in 2014-2019. The sample of this research is 10 companies and the model used in this research is multiple linear regression. The results of cash flow have no effect on firm value in the Food and Beverages consumer industry sector companies listed on the Indonesia Stock Exchange in 2014-2019. Meanwhile, financial leverage and current ratio have an effect on company value in the Food and Beverages consumer industry sector companies listed on the Indonesia Stock Exchange in 2014-2019